Model Pendidikan Pancasila dan Bela Negara di UPN Veteran Yogyakarta dalam Menjawab Tantangan Kebangsaan - Lestanta Budiman; Hari Dwi Laksana; Hastangka Hastangka (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aims to analyze the education model of Pancasila and National Defense in UPN Veteran. The research used descriptive method with a qualitative approach. The research was conducted in UPN Veteran Yogyakarta with its university student as the subject of the research. Data of the research were obtained through empirical and critical study and observation of Pancasila and National Defense learning. The primary data were obtained through interviews while the secondary data were obtained through literature reviews. The analysis technique used deductive-inductive analysis technique. The result of the research showed that the Pancasila and National Defense education model developed in UPN Veteran Yogyakarta consisted of two ways which were co-curricular and extracurricular programs.